Against the standard - Cubel, Maria; Sanchez-Pages, Santiago; Schwieren, Christiane; Steck, Cosima-Valerie (AWI discussion paper series, 2025)
Extensive research has documented gender differences in the willingness to compete against others. Less attention has been given to situations where individuals must meet a standard of excellence to obtain rewards, such as promotions, grants, and publications. This paper investigates gender differences in competing against such standards through a laboratory experiment. Participants completed two rounds of a multiple-choice test. After the first round, they received feedback on whether they met a top-quartile performance threshold set by a reference group. Before the second round, they had to choose between a piece rate payment or a higher rate contingent upon surpassing the threshold. We compared choices across a control treatment with no feedback and three feedback conditions with varying standards: objective peer performance, peer expectations, and expert expectations. Results show that without feedback, women are less likely than men to benchmark against the standard. Feedback closes this gap when the standard is set by peers, but not when set by experts. A theoretical model and an out-of-experiment study suggest these differences stem from gendered priors about ability and asymmetric belief updating. These findings offer insights into gender differences in self-promotion and suggest ways feedback might mitigate these differences.
Keywords: Graue Literatur